Escape from empire : the developing world's journey through heaven and hell - Amsden, Alice H. (Alice Hoffenberg) (MIT Press, 2007)
In Escape from Empire, Alice Amsden argues that the more freedom a developing country has to determine its own policies, the faster its economy will grow. America's recent inflexibility - as it has single-mindedly imposed the same rules, laws, and institutions on all developing economies under its influence - has been the backdrop to the rise of two new giants, China and India, who have built economic power in their own way.